Factors Affecting Environmental Performance: A Study of IKEA - Alrubah, Sarah Abduallah; Alsubaie, Lulwa Khalied; Quttainah, Majdi Anwar; Pal, Monika; Pandey, Rudresh; Shamiliy, Thiagarajan A/P; Kee, Daisy Mui Hung; Ling, Lee Kuong; Nadirah, Nour Aliaa; Aishan, Norfathu (AIBPM Publisher, 2020)
IKEA is a Swedish multinational group that provides home services and sells ready-to-assemble furniture, kitchen appliances, and home accessories. Several factors can emphasize the success of a company such as brand loyalty, the company's status, and the products and services. These success factors give various benefits to customers and to the company itself. The purpose of this proposal is to examine the success factor of IKEA in terms of environmental performance aspect. This case picked will be mainly in Asia. The study used secondary data to collect data from the Internet which are journals and articles from the IKEA branches in Malaysia. Also, we want to know how IKEA provides strategic approaches to improve the company.